USING ENGLISH COMICS TO TEACH READING IN EFL CLASSROOMS - Habeahan, Elizabet (ELTR Journal, 2025)
Reading is essential in language development, mainly when learning and teaching English as a Foreign Language (EFL). In that case, few studies have explored using English comics as a reading-learning method for EFL students, specifically in Indonesian schools. In response, the researcher was interested in exploring the teachers' perspectives on using comics to teach reading in EFL classrooms, its benefits, challenges, and how to overcome the challenges. To meet the research objectives, the researcher first conducted a literature review of 18 articles published in national and international journals. The articles were explored from SINTA, Google Scholar, and EBSCO databases. The researcher then interviewed three teachers to discuss the literature review analysis results. The findings reveal that teachers perceive comics as beneficial for enhancing students’ reading engagement and comprehension in EFL classrooms. However, teachers’ challenges include a lack of exposure to digital comic resources, technological limitations, and the need for training in digital comic integration. Some students, particularly those with lower proficiency, also experience difficulties interpreting visual and textual information. Teachers suggested adequate support, including professional development and access to appropriate digital tools, as essential for maximizing the potential of comics in learning EFL teaching. Directions for further research are presented.